(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Human capital refers to the stock of personal and social attributes that are integrated in the ability to generate economic values. The process of acquiring and increasing the number of persons with such personal and social attributes that are prerequisites for economic development of a country is human capital formation. The problem of human capital formation is acute across the globe, but it has its highest intensity in overpopulated developing countries like India. Although India is a thickly populated country, there is a dearth of human capital owing to its demographic structure on one hand and lack of facilities needed to form human capital on the other. Rural India, particularly rural Odisha, is a step ahead in this count, as the rural population is very high in the country and the skill set required to create economic values is rare to find there. As such, avenues for engaging rural masses in Odisha are not alluring, and with the lack of befitting skills to contribute to household management, people from rural Odisha are migrating to other states of the country and even to other countries. Due to migration, no doubt, the rural sector is getting relaxed a bit on the ground that those migrants are no more in need of getting absorbed in the labor market. The question that laid the foundation of this Paper is - ‘Does migration influence the status of human capital formation?’